Long-Lasting Effects of Prenatal Ethanol Exposure on Fear Learning and Development of the Amygdala - Kozanian, Olga O.; Rohac, David J.; Bavadian, Niusha; Corches, Alex; Korzus, Edward; Huffman, Kelly J. (Frontiers in Behavioral Neuroscience, 2018)
Prenatal ethanol exposure (PrEE) produces developmental abnormalities in brain and behavior that often persist into adulthood. We have previously reported abnormal cortical gene expression, disorganized neural circuitry along with deficits in sensorimotor function and anxiety in our CD-1 murine model of fetal alcohol spectrum disorders, or FASD (El Shawa et al., 2013; Abbott et al., 2016). We have proposed that these phenotypes may underlie learning, memory, and behavioral deficits in humans with FASD. Here, we evaluate the impact of PrEE on fear memory learning, recall and amygdala development at two adult timepoints. PrEE alters learning and memory of aversive stimuli; specifically, PrEE mice, fear conditioned at postnatal day (P) 50, showed deficits in fear acquisition and memory retrieval when tested at P52 and later at P70–P72. Interestingly, this deficit in fear acquisition observed during young adulthood was not present when PrEE mice were conditioned later, at P80. These mice displayed similar levels of fear expression as controls when tested on fear memory recall. To test whether PrEE alters development of brain circuitry associated with fear conditioning and fear memory recall, we histologically examined subdivisions of the amygdala in PrEE and control mice and found long-term effects of PrEE on fear memory circuitry. Thus, results from this study will provide insight on the neurobiological and behavioral effects of PrEE and provide new information on developmental trajectories of brain dysfunction in people prenatally exposed to ethanol.